Targeted Deletion and Lipidomic Analysis Identify Epithelial Cell COX-2 as a Major Driver of Chemically-induced Skin Cancer - Jiao, Jing (Mol Cancer Res, 2014)
Pharmacologic and global gene deletion studies demonstrate that cyclooxygenase-2 (PTGS2/COX2) plays a critical role in DMBA/TPA-induced skin tumor induction. While many cell types in the tumor microenvironment express COX-2, the cell types in which COX-2 expression is required for tumor promotion are not clearly established. Here, cell-type specific Cox-2 gene deletion reveals a vital role for skin epithelial cell COX-2 expression in DMBA/TPA tumor induction. In contrast, myeloid Cox-2 gene deletion has no effect on DMBA/TPA tumorigenesis. The infrequent, small tumors that develop on mice with an epithelial cell-specific Cox-2 gene deletion have decreased proliferation and increased cell differentiation properties. Blood vessel density is reduced in tumors with an epithelial cell-specific Cox-2 gene deletion, compared to littermate control tumors, suggesting a reciprocal relationship in tumor progression between COX-2 expressing tumor epithelial cells and microenvironment endothelial cells. Lipidomics analysis of skin and tumors from DMBA/TPA-treated mice suggests that the prostaglandins PGE2 and PGF2α are likely candidates for the epithelial cell COX-2-dependent eicosanoids that mediate tumor progression. This study both illustrates the value of cell-type specific gene deletions in understanding the cellular roles of signal-generating pathways in complex microenvironments and emphasizes the benefit of a systems-based lipidomic analysis approach to identify candidate lipid mediators of biological responses.